2021
DOI: 10.1038/s41598-021-00037-8
|View full text |Cite
|
Sign up to set email alerts
|

Nondetrimental impact of two concomitant entomopathogenic fungi on life history parameters of a generalist predator, Coccinella septempunctata (Coleoptera: Coccinellidae)

Abstract: The non-persistent impact of biocontrol agents can be revealed for pest control when associated entomopathogenic fungi (EPFs) negatively affect the natural enemies. In this assay, impacts of Beauvaria bassiana (Balsamo) Vuillemin, and Metarhizium anisopliae (Metschnikoff) Sorokin were studied for their compatibility or side effects on life table parameters of an important generalist predator, Coccinella septempunctata L. The results indicated non-significant impacts of both EPFs on life table parameters of C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The other biopesticides were very much safe for the coccinellids population in the present study, which is also supported by several other previous studies. M. robertsii could be used as a potential biocontrol agent against insect pests, since it was found to be relatively safe for natural enemies [91][92][93]. Fatiha et al [94] reported that there was no effect of Verticillium lecanii on different biological parameters of the coccinellid predator (Serangium japonicum) of whiteflies.…”
Section: Discussionmentioning
confidence: 99%
“…The other biopesticides were very much safe for the coccinellids population in the present study, which is also supported by several other previous studies. M. robertsii could be used as a potential biocontrol agent against insect pests, since it was found to be relatively safe for natural enemies [91][92][93]. Fatiha et al [94] reported that there was no effect of Verticillium lecanii on different biological parameters of the coccinellid predator (Serangium japonicum) of whiteflies.…”
Section: Discussionmentioning
confidence: 99%
“…Entomopathogenic fungi, B. bassiana and M. anisopliae were obtained from AgriLife SOM Phytopharma (Hyderabad, Telangana. India) Limited in talc form [25]. The conidial spore suspension for both fungi was adjusted to 1 × 10 8 conidia mL −1 by using Neubauer hemocytometer [26].…”
Section: Entomopathogenic Fungimentioning
confidence: 99%